The Independence of Post Sectio Caesarea Mother with Discharge Planning Based on Orem's Self Care Theory - Tinok Ayu Putri W; Nursalam Nursalam; Eka Mishbahatul Mar'ah Has (Jurnal Ners, 2012)
Introduction: Discharge planning is one of nursing intervention that aim to promote the independence of patient's self care-activities after discharge from hospital. This study was aimed to examine the effect of discharge planning on wound care independence of post sectio caesarea mother at Melati Room, Dr. Soegiri Hospital, Lamongan.Method: Design of this study was quasy experiment. The population were post sectio caesarea mother at Melati Room Dr. Soegiri Hospital Lamongan, since May – June 2012. The samples were taken by purposive sampling technique. Fourteen responsdents matched with the inclusion criteria and divided into treatment and control groups. The datas were collected by using questionnaire and observation sheet. Then datas were analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with signiﬁcance level of α ≤ 0.05.Result: The result of this study showed that post sectio caesarea mother knowledge had signiﬁcance level of p = 0.027 in treatment group, and in control group was p = 0.034, for post sectio caesarea patient's skill p = 0.015 in treatment group and in control group was p = 0.017. The result of Mann Whitney U test was p = 0.001, it means there was different in knowledge, and skill of wound care on post sectio caesarea patient between treatment and control groups.Discussion: It can be concluded that there are signiﬁcant effect of wound care independence of post sectio caesarea patient with discharge planning approach based on orem's self care theory to improve patient's independence. Hospital need to develop discharge planning procedure to meet the needs of patient with post sectio caesarea wound and decrease the number of surgical wound infection.